Nature and the Greeks and Science and humanism - Schrodinger, Erwin (Cambridge University Press, 1996)
Nobel laureate Erwin Schrödinger was one of the most distinguished scientists and philosophers of the twentieth century, and his lectures are legendary. Here the texts of two of Schrödinger's most famous lecture series are made available again. In the first, entitled "Nature and the Greeks," Schrödinger offers a historical account of the scientific world picture. In the second, called "Science and Humanism," he addresses fundamental questions about the link between scientific and spiritual matters. As Roger Penrose confirms, these are the profound thoughts of a great mind, and as relevant today as when they were first published in the 1950s